The metastasis-associated protein S100A4 promotes the inflammatory response of mononuclear cells via the TLR4 signalling pathway in rheumatoid arthritis. (18th March 2014) - Cerezo, Lucie Andrés; Remáková, Martina; Tomčik, Michal; Gay, Steffen; Neidhart, Michel; Lukanidin, Eugene; Pavelka, Karel; Grigorian, Mariam; Vencovský, Jiří; Šenolt, Ladislav
Abstract : Objectives. S100A4 has been implicated in cancer and several inflammatory diseases, including RA. The aim of the present study was to determine whether S100A4 can stimulate proinflammatory cytokine production in mononuclear cells. Methods. Peripheral blood mononuclear cells (PBMCs) isolated from patients with RA were stimulated with S100A4, S100A8, S100A9 and S100A12. The production of IL-1β, IL-6 and TNF-α was measured by ELISA. Receptor for advanced glycation end products (RAGEs) and Toll-like receptor 4 (TLR4) signalling were examined. For signalling pathway blocking studies, inhibitors of myeloid differentiation primary response gene 88 (MyD88), nuclear factor kappa B (NF-κB) and the mitogen activated protein (MAP) kinases p38, extracellular signal-regulated kinase 1/2 (ERK1/2) and Jun N-terminal kinase (JNK) were used. MAP kinase activation was evaluated by western blotting. Results. Stimulation of PBMCs with S100A4 significantly up-regulated IL-1β, IL-6 and TNF-α production compared with unstimulated cells ( P < 0.001). Importantly, the production of these cytokines was markedly enhanced in response to S100A4 compared with S100A8 and S100A12; however, it was less pronounced compared with S100A9. Furthermore, enhanced production of proinflammatory cytokines in S100A4-stimulated PMBCs was at least partly mediated via TLR4, but not RAGEs, and by activation of the transcription factor NF-κB and the MAP kinases p38 and ERK1/2. Conclusion. This is the first study to demonstrate that S100A4 can induce an inflammatory response mediated by TLR4 and by the activation of NF-κB and the kinases p38 and ERK1/2 in mononuclear cells from patients with RA. Therefore S100A4 may be a potential therapeutic target for immune-mediated diseases.